Identification of stromal cell proportion-related genes in the breast cancer tumor microenvironment using CorDelSFS feature selection: implications for tumor progression and prognosis - Guo, Sicheng; Ma, Yuting; Li, Xiaokang; Li, Wei; He, Xiaogang; Yuan, Zheming; Hu, Yuan (Frontiers in Genetics, 2023)
The breast cancer (BRCA) tumor microenvironment (TME) is a dynamic microecosystem with complex cell components and molecular mechanisms affecting the occurrence, progression, and prognosis of BRCA. However, as the tumor progresses, the dynamic changes of stromal and immune cells in TME become unclear. Herein, genes consisting of differentially co-expressed genes (DCGs) predicted for stromal cell proportion (TME-key DCGs) were identified by integrating a new heuristic feature selection strategy (CorDelSFS) and combining it with differential co-expression analysis. TME-key DCGs could mimic the dynamic trend of BRCA TME, while its co-expression network formed cell type-specific subnetworks. The IG gene-related subnetwork, plasmablast-specific expression, presented completely different expression patterns in different TMEs and played a key role in the BRCA TME via its adaptive immune function and tumor progression inhibition. Besides, the prognostic model constructed by six prognostic genes in TME-key DCGs showed that the risk score was significantly correlated with the proportion of stromal cells and immune cells in TME, and low-risk patients were hereby observed to have stronger adaptive immune function. Overall, IGKV1D-39 is considered a novel BRCA prognostic marker specifically expressed in plasmablasts and involved in adaptive immune responses, which provides new prognostic value and potential immunotherapy targets for clinical application.